Printed transducers using nanomaterials for gas sensing. (2019) - Debéda, Hélène; Nguyen, Van Son; Clément, Pierrick; Jubera, Véronique; Llobet, Eduard
Abstract: New generation of room temperature screen-printed gas sensors based on either gas sensitive semiconductive ZnO nanoparticles or on free-standing cantilevers coated with a carbon nanotube sensitive layer are herein proposed. The first type is using ZnO nanoparticles printed and sintered at 400°C on interdigitated Pt electrodes. Instead of UV LED activation giving a sensitivity improvement at room temperature, halogen lighting activation yields a good sensitivity, comparable to those given in the literature. The second type is using resonating MEMS based on piezoelectric Au/PZT/Au cantilevers coated with CNTs.. In this case, another transducing mechanism is added onto the cantilever thanks to a top interdigitated electrodes allowing both the simultaneous measurement of the resonance frequency shifts of the cantilever and the resistance variations of the resistive sensitive coating.